The Italian Archaeological Expedition to Qasr Shamamuk-Kilizu, Iraq, 1933. Notes on the Excavation Finds at the Iraq Museum in Baghdad - Anastasio, Stefano (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
In 1933, an Italian archaeological expedition carried out an excavation at the Assyrian Kilizu, today Qasr Shamamuk in northern Iraq, halfway between the Greater Zab and Erbil. The expedition was directed by the assyriologist Giuseppe Furlani, who was assisted by the archaeologist Doro Levi. It lasted two months, from 24 February to 21 April 1933, and several areas either on the tell, in the lower town and in the surrounding area were investigated during this campaign. The main result of the expedition was the excavation of a large necropolis immediately west of the tell. Forty-four burials were found in an area of about 20x17 m, mainly dating to the ‘Assyrian’ (i.e. Middle- and Late-Assyrian, according to the artefacts) and Parthian periods.